Staphylococcal cassette chroromosome mec (SCCmec) typing of methicillin-resistant Staphylococcus aureus (MRSA) isolates from patients attending Tengku Ampuan Afzan hospital (HTAA) in Kuantan, Pahang, Malaysia - Mustafa, M. I; Alarosi, N. A.; Mohammad Amjad, Nasser (Elsevier, 2012)
Background: The adaptive power of Staphylococcus aureus to antibiotics lead to the emergence of methicillin-resistant S. aureus (MRSA) in the early 1960s. The cause of resistance to methicillin is the acquisition of the mecA gene, situated on a mobile genetic element called the staphylococcal cassette chromosome mec (SCCmec). Methods: One of the most important techniques used to investigate the molecular epidemiology of S. aureus is SCCmec typing. This technique has been used to study the evolution of the MRSA and to study their subsequent worldwide dissemination. Twenty-eight MRSA isolates were subjected toSCCmec typing by duplex real time PCR. The MRSAs were isolated by the Bacteriology Laboratory in Hospital Tengku Ampuan Afzan (HTAA), Kuantan, Pahang, Malaysia from inpatients admitted during the period from 1stApril to 30th September, 2010. The MRSA isolates were re-identified by known bacteriological methods and the minimal inhibitory concentration (MIC) of oxacillin was determined by E-test. The antibiotic susceptibility was tested, by disc diffusion method to 7 different antibiotics. Results: Four major sites were listed (Fig 3): skin and soft tissue infections 14 (50%), ENT infections 7 (25%), respiratory tract infections 1 (3.57%), blood stream infections 5 (17.85%), and other body fluids 1 (3.57%).Resistance to oxacillin was 100%, with an MIC >4 μg/mL. Resistance to other antibacterial drugs was erythromycin 82.1%, gentamicin 75%, tetracycline 78.6%, and trimethoprim-sulfamethoxazole 78.6%. None of the isolates was resistant to vancomycin or chloramphenicol. 78.5% (22/28) were shown to be of SCCmec-type III and 21.5% (6/28) were of type IV. Conclusion: The results confirm observations in several other neighboring Far Eastern countries and corroborates the epidemicity of these two SCCmec types in Kuantan, Malaysia.